2010
DOI: 10.1016/j.pbb.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Flunitrazepam in combination with alcohol engenders high levels of aggression in mice and rats

Abstract: Rationale Higher doses of benzodiazepines and alcohol induce sedation and sleep; however, in low to moderate doses these drugs can increase aggressive behavior. Objectives To assess firstly the effects of ethanol, secondly the effects of flunitrazepam, a so-called club drug, and thirdly the effects of flunitrazepam plus alcohol on aggression in mice and rats. Methods Exhaustive behavioral records of confrontations between a male resident and a male intruder were obtained twice a week, using CF-1 mice and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previous studies have reported that alcohol intoxication following acute (single dose) as well as chronic ethanol (multiple experimenter-administered, p.o.) increased aggression-like behavior in (intoxicated) rodents in a resident-intruder confrontation paradigm (de Almeida et al, 2010; Peterson et al, 1989). High aggression in this paradigm was associated with increased anxiety and increased plasma CORT (Patki et al, 2015; Peterson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that alcohol intoxication following acute (single dose) as well as chronic ethanol (multiple experimenter-administered, p.o.) increased aggression-like behavior in (intoxicated) rodents in a resident-intruder confrontation paradigm (de Almeida et al, 2010; Peterson et al, 1989). High aggression in this paradigm was associated with increased anxiety and increased plasma CORT (Patki et al, 2015; Peterson et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral experiments were performed in the period from the 24 th till the 29 th day of the experiment and during the light cycle from 8 a.m. till 5 p.m. (de Almeida et al, 2010). After the last dose on day 30, all rats were weighed then sacrificed by decapitation.…”
Section: Experimental Designmentioning
confidence: 99%
“…Controlled laboratory studies have demonstrated that alprazolam and diazepam use can result in an increased aggressive response in some participants (e.g., Bond and Silveira, 1993;Bond et al, 1995;Ben-Porath and Taylor, 2002;Wallace and Taylor, 2009), and animal studies report the possible influence of concurrent alcohol use (de Almeida et al, 2010) and pre-existing aggressive tendencies (Ferrari et al, 1997;Weerts et al, 2010) in benzodiazepine-related aggression.…”
Section: Introductionmentioning
confidence: 99%